Sub-daily meteorological series of Riva del Garda (1872-01-01 - 1888-10-31) - Brugnara, Yuri (In: Brugnara, Y (2025): Sub-daily meteorological series of Riva del Garda (1872-1915) [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.984693, 2025)
The station of Riva, established in June 1869, was one of the synoptic (or first-order) stations of Austria-Hungary and the only one in South Tyrol. Synoptic stations sent their data to the central meteorological office in Vienna once a day via telegraph to be used for weather forecast. The data were retransmitted to other European weather services and, starting from 1872, were also published on the yearbooks of the K.K. Central-Anstalt für Meteorologie and Geomagnetismus, from where the data have been digitized. The following variables are provided: temperature, daily maximum temperature, daily minimum temperature, pressure, relative humidity, cloud cover, wind intensity and direction, precipitation amount and type. Most variables (except daily extremes and precipitation) were measured three times per day. The instruments were provided by the Central-Anstalt (weather service) and were read manually by the director of the local gymnasium. The barometer was periodically compared with a standard reference, therefore the quality of the measurements was very high even by today's standard. However, thermometers at the time were insufficiently shielded from radiation, causing warm biases in certain situations. The measurements were discontinued with the war declaration of Italy on Austria-Hungary in May 1915, as Riva laid directly on the front line.
Keywords: air pressure; cloud cover; humidity; Lake Garda; precipitation; Temperature; weather data; wind